2013
DOI: 10.5402/2013/945254
|View full text |Cite
|
Sign up to set email alerts
|

Orofacial Clefts: A Clinical Community Study in a Developing Country

Abstract: Aim. The study aimed at finding the types of orofacial clefts, reasons for delay in the repair of the deformity and medium through which patients and/or their relatives heard about the outreach program. Methods. This study was from 2009 to 2011 at two different study sites. The team visited various media houses and health facilities at each study site to disseminate information concerning the cleft outreach program. Patients and/or their parents who visited the hospitals were interviewed using a questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Regarding the common reason for the delay in presenting for surgical intervention, most of our patients cited their inability to offset the cost of cleft surgery as the primary factor protracting their care seeking. The proportion of these participants is similar to the observations of Adeyemo et al (2009) in Nigeria and Agbenorku et al (2013) in Ghana, where 47.5% and 56.7% of their patient population alluded to the lack of finance as the main reason for late presentation. Collectively, this observation reflects the effect of the socioeconomic state of these developing countries especially within sub-Saharan Africa on the cleft-care seeking behavior of patients or their caregivers and the endemic nature of "lack of finance" as a barrier to surgical repair.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Regarding the common reason for the delay in presenting for surgical intervention, most of our patients cited their inability to offset the cost of cleft surgery as the primary factor protracting their care seeking. The proportion of these participants is similar to the observations of Adeyemo et al (2009) in Nigeria and Agbenorku et al (2013) in Ghana, where 47.5% and 56.7% of their patient population alluded to the lack of finance as the main reason for late presentation. Collectively, this observation reflects the effect of the socioeconomic state of these developing countries especially within sub-Saharan Africa on the cleft-care seeking behavior of patients or their caregivers and the endemic nature of "lack of finance" as a barrier to surgical repair.…”
Section: Discussionsupporting
confidence: 80%
“…Further, our findings buttress the report of Ajike et al (2013), who reported a similar experience with 41.8% of their cases indicating "family and relatives" as their source of information. Studies by Agbenorku et al (2013) and Aziz et al (2009) however recorded contrasting findings in that the former, in a study conducted in rural Ghana, reported "hospital referral" (32.8%) as the commonest source of information indicated by their participants, while Aziz et al (2009) reported that majority of their study participants were recruited through adverts posted on print media platforms. Although this appears to be dependent on the characteristics of the target population, we recommend the adoption of low-cost, person-contact information dissemination methods for community penetrance in future surgical missions.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…of what to expect at the cleft clinic agreed with a study in developing countries, where factors such as cultural beliefs, superstitions, lack of awareness of treatment services, and lack of time have been reported to contribute to delayed presentation of CL ± P patients[23] [24].…”
mentioning
confidence: 68%